Silty Clay Stabilization Using Metakaolin-Based Geopolymer Binder - Wang, Shengnian; Su, Jun; Wu, Zhijian; Ma, Wei; Li, Yue; Hui, Honglei (Frontiers in Physics, 2021)
Geopolymer binders are adjudged as the latest wave of sustainable alkali-activated materials for soil stabilization due to their excellent bonding properties. This study applied metakaolin as a precursor for synthesizing the geopolymer binder by employing the mixture of quicklime and sodium bicarbonate as an alkali-activator. The optimal mass mixing ratio of the alkali-activator, metakaolin, and silty clay was determined by unconfined compression tests. The stabilization mechanisms of the geopolymer binder were measured by X-ray Diffraction and Fourier Transform Infrared spectroscopy. The microstructural characteristics of the geopolymer-stabilized silty clay were observed by Scanning Electron Microscopy with an Energy Dispersive X-ray spectroscopy and Mercury Intrusion Porosimetry test for understanding the strengthening mechanism of the silty clay after the treatment. Results indicate that the optimal mass mixing ratio of the alkali-activator, metakaolin, and silty clay is 1:2:17, and the unconfined compressive strength of the geopolymer-stabilized silty clay reaches the maximum value of 0.85 MPa with adding 15 wt% of the geopolymer binder. Diffraction patterns show an insufficient polymerization of the geopolymer binder in the silty clay in the early days but a rapid synthesis of aluminosilicate gels after that. The new asymmetrical stretching vibration peaks signified the formation of aluminosilicate networks and are responsible for the strength improvement of the silty clay. Microstructural analyses further confirm the formation of aluminosilicate gels and their positive impacts on the structure of the silty clay over curing age.